Exploring State Policy Regarding Teachers Removing License Endorsements: Short Term and Long Term Policy Implications. Vol. 13 No. 47 - Earley, Penelope; Brazer, S. David (Education Policy Analysis Archives, 2005)
This study explores and begins baseline documentation of state policies governing teachers' voluntary removal of endorsement areas from their licenses. Through a survey of state licensure officers we find that most states allow teachers to remove endorsements, though the specifics of how this can be done vary from state to state. The No Child Left Behind Act and the Individuals With Disabilities Education Act may help motivate teachers to remove endorsements. By defining teacher qualifications and setting expectations that all students will achieve adequate yearly progress on state examinations, these two pieces of legislation place additional pressure on teachers of general population and at-risk students. Thus, federal policy contributes to a dilemma playing out at the state level: Policies enacted to improve classroom instruction may increase pressure on qualified teachers that potentially drives some of them away from special needs classrooms that most require high quality service. As demands on them mount, teachers may look for ways to relieve some stress points. Removing a license endorsement becomes one such tool to avoid teaching in classrooms of students with learning challenges. If significant numbers of teachers remove license endorsements, labor market dislocations may follow. Additional study is needed in the future to further document how states do or do not regulate endorsement removal, the extent to which teachers are aware of and have utilized this option, and how school, district, and state administrators and decision makers respond to license endorsement removal.